Plumbagin Prevents Secretory Diarrhea by Inhibiting CaCC and CFTR Channel Activities - Yu, Bo; Zhu, Xiaojuan; Yang, Xinyu; Jin, Lingling; Xu, Jia; Ma, Tonghui; Yang, Hong (Frontiers in Pharmacology, 2019)
Secretory diarrhea, which primarily originates through intestinal pathogens and viruses, is a health burden in many regions worldwide. Enterocyte Cl− channels, as the final step in enterotoxin-induced fluid secretion, constitute an attractive class of targets for diarrhea therapy. Chloride channel inhibitors have become a new class of candidates for anti-secretion and anti-intestinal motility agents. In the present study, we identified plumbagin as a TMEM16A inhibitor in a cell-based fluorescence-quenching assay, the IC50 value was ~12.46 μM. Short-circuit current measurements showed that plumbagin reversibly inhibited the Eact-induced Cl− current on the apical side of TMEM16A-transfected FRT cells with no significant effect on cytoplasmic Ca2+ signaling. Notably, plumbagin also inhibited the activity of intestinal epithelial calcium-activated chloride channel (CaCC) and cystic fibrosis transmembrane conductance regulator (CFTR) in both HT-29 cells and mouse colons, but had no effects on the activity of the Na+-K+ ATPase or K+ channels. In in-vivo experiments, the administration of plumbagin reduced both Escherichia coli heat-stable enterotoxin (STa)- and cholera toxin (CT)-induced intestinal fluid secretion. In neonatal mouse models of cholera toxin- and rotavirus infection-induced diarrhea, 0.4 μg plumbagin inhibited secretory diarrhea by >40% and 50%, respectively, without affecting intestinal epithelial integrity or the rotaviral infection. In addition, plumbagin exerted inhibitory effects on the vasoactive intestinal peptide (VIP)-, prostaglandin E2 (PGE2)- and 5-hydroxytryptamine (5-HT)-stimulated Cl− currents. In the evaluations of intestinal motility, plumbagin significantly delayed intestinal motility and inhibited intestinal smooth muscle contractility without an evident impact on contractive frequency. Collectively, our results indicate that plumbagin inhibits both Ca2+- and cAMP-activated Cl− channels, accounting for the mechanisms of plumbagin inhibition of chloride secretion and intestinal motility. Thus, plumbagin can be a lead compound in the treatment of cholera toxin-induced, Traveler’s and rotaviral diarrhea as well as other types of secretory diarrhea that result from excessive intestinal fluid secretion and increased intestinal peristalsis.